Exogenous Calcium Enhances the Photosystem II Photochemistry Response in Salt Stressed Tall Fescue - Wang, Guangyang; Bi, Aoyue; Amombo, Erick; Li, Huiying; Zhang, Liang; Cheng, Cheng; Hu, Tao; Fu, Jinmin (Frontiers in Plant Science, 2017)
Calcium enhances turfgrass response to salt stress. However, little is known about PSII photochemical changes when exogenous calcium was applied in salinity-stressed turfgrass. Here, we probe into the rearrangements of PSII electron transport and endogenous ion accumulation in tall fescue (Festuca arundinacea Schreber) treated with exogenous calcium under salt stress. Three-month-old seedlings of genotype ‘TF133’ were subjected to the control (CK), salinity (S), salinity + calcium nitrate (SC), and salinity + ethylene glycol tetraacetic acid (SE). Calcium nitrate and ethylene glycol tetraacetic acid was used as exogenous calcium donor and calcium chelating agent respectively. At the end of a five-day duration treatment, samples in SC regime had better photochemistry performance on several parameters than salinity only. Such as the Area (equal to the plastoquinone pool size), N (number of QA- redox turnovers until Fm is reached), E0 or δRo (Efficiency/probability with which a PSII trapped electron is transferred from QA to QB or PSI acceptors), ABS/RC (Absorbed photon flux per RC). All the above suggested that calcium enhanced the electron transfer of PSII (especially beyond QA-) and prevented reaction centers from inactivation in salt-stressed tall fescue. Furthermore, both grass shoot and root tissues generally accumulated more C, N, Ca2+, and K+ in the SC regime than S regime. Interrelated analysis indicated that E0, δRo, ABS/RC, C and N content in shoots was highly correlated to each other and significantly positively related to Ca2+ and K+ content in roots. Besides, high salt increased ATP6E and CAMK2 transcription level in shoot at 1 day and 5 day respectively while exogenous calcium relieved it. In root，CAMK2 level was reduced by Salinity at 5 day and exogenous calcium recovered it. These observations involved in electron transport capacity and ion accumulation assist in understanding better the protective role of exogenous calcium in tall fescue under salt stress.